Large radiopaque lesion in the posterior mandible: A challenging case - B Sasirekha; Philips Mathew; M Ganeshkumar; Ravi David Austin; Raj Prabhu (Journal of Pharmacy and Bioallied Sciences, 2016)
Radiopaque lesions of the jawbones are frequently encountered in dental radiographs. A variety of conditions such as chronic inflammation, soft tissue calcifications, fibrosseous lesions, odontogenic tumors, and bone neoplasms can manifest as radiopaque lesions on the jawbones. These radiopaque lesions are often difficult to distinguish from each other, hence making the formulation of differential diagnosis challenging. A thorough patient's history and clinical examination supplemented by appropriate investigations will enable the clinician in narrowing down the differential diagnosis and to identify the condition accurately. Presented here is a case of the large radiopaque lesion on posterior mandible surrounded by lytic areas in a 20-year-old male patient.